An evaluation of curriculum changes in engineering graphics - Zlatko Gradinscak; William P. Lewis (1995)
The presentation of technical information graphically through the use of sketches, mechanical drawings, and CAD systems is a fundamental part of engineering practice. Differences in background experience and gender cause many individuals to possess impaired ability to spatially visualise solutions to problems. However, these abilities can be developed and enhanced through both formal educational and informal experiences. The development and integration of a computer-based visualisation course was initiated at RMIT in the 1992 as part of departmental educational effort to advance engineering graphics instruction. The problem of determining the effectiveness of various engineering graphics educational aids in developing students' spatial abilities was addressed in a research project that started in 1993. The paper discusses the research project, presents findings from the study, reviews the engineering graphics course offered to all first year engineering students in 1993 and 1994, and recommends future developments.